2011
DOI: 10.1016/j.bbamcr.2010.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule studies of nucleocytoplasmic transport

Abstract: Molecular traffic between the cytoplasm and the nucleoplasm of eukaryotic cells is mediated by nuclear pore complexes (NPCs). Hundreds, if not thousands, of molecules interact with and transit through each NPC every second. The pore is blocked by a permeability barrier, which consists of a network of intrinsically unfolded polypeptides containing thousands of phenylalanine-glycine (FG) repeat motifs. This FG-network rejects larger molecules and admits smaller molecules or cargos bound to nuclear transport rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 110 publications
3
36
0
Order By: Relevance
“…5C). The mean transit time is relatively unchanged over a large range of cargo sizes even as macroscopic transport rate decreases, a prediction recently verified in a paper published while this manuscript was in review (19). For cargo >18-nm diameter, there was a substantial increase in the transit time.…”
Section: Brownian Ratchet Predicts That Fg-nup Structure Effects Transupporting
confidence: 52%
See 1 more Smart Citation
“…5C). The mean transit time is relatively unchanged over a large range of cargo sizes even as macroscopic transport rate decreases, a prediction recently verified in a paper published while this manuscript was in review (19). For cargo >18-nm diameter, there was a substantial increase in the transit time.…”
Section: Brownian Ratchet Predicts That Fg-nup Structure Effects Transupporting
confidence: 52%
“…For the 10-ring system (Table S2), stabilizing FG-FG interactions slowed transport rate by >50% (325 to 114∕s) and increased the mean transit time by approximately 33% (27 to 35 ms). Note that individual non-NLS-cargo molecules transited faster than NLS cargo, a prediction that has also been verified while this manuscript was in review (19), representing the fact that free diffusion around FG-Nups is faster than transport mediated by binding to the Nups. NLS cargo, after all, is slowed down by the actual events of binding and RanGTP-mediated unbinding.…”
Section: Brownian Ratchet Predicts That Fg-nup Structure Effects Tranmentioning
confidence: 70%
“…[3][4][5] Although large ribonucleoprotein complexes were recently reported to be exported from the nucleus through nuclear membrane budding, 6 the majority of the bidirectional trafficking of macromolecules between the nucleus and the cytoplasm is still believed to be mediated by thousands of nuclear pore complexes (NPCs) embedded in the NE. [7][8][9][10][11][12][13][14][15][16] As revealed by electron microscopy, the architecture of the NPC consists of a central scaffold region with an approximate length of 40-90 nm and an inner diameter of 50 nm, multiple flexible fibrils extending approximately 50 nm into the cytoplasm and a basket structure that protrudes approximately 75 nm into the nucleus. [17][18][19][20][21] The NPC is a large assemblage composed of approximately 30 different proteins, each of which is present in multiples of eight copies, known disputes between these models focus on at least three critical questions: (1) is there a single diffusion channel or are there multiple channels for small molecules in the NPC, (2) do passive and facilitated transport display spatially and functionally separate or shared pathways and (3) do the transport receptors collapse or dissolve the selective barrier formed by FG filaments in the NPC?…”
Section: Npc Structure and Functionmentioning
confidence: 99%
“…toplasmic faces of NPCs promote key assembly and disassembly steps at the beginning or end of cargo transport (for reviews, see refs. [22][23][24]. However, because transport occurs in the millisecond time regime, it is unclear to what extent these in vitro biochemical results relate to the rapid kinetics that occur during transport through intact NPCs.…”
mentioning
confidence: 99%
“…A high nuclear RanGTP concentration and low cytoplasmic RanGTP concentration drive both import and export. In principle, translocation through the NPC and the assembly and disassembly of transport complexes can be disconnected processes, although greater transport efficiencies are expected if these processes are coupled (22). Numerous studies have indicated that proteins found on the nucleoplasmic and cySignificance Nucleocytoplasmic transport requires the orchestrated assembly and disassembly of cargo-carrier complexes.…”
mentioning
confidence: 99%